2000
DOI: 10.1002/1097-4660(200010)75:10<869::aid-jctb285>3.0.co;2-i
|View full text |Cite
|
Sign up to set email alerts
|

Post-transcriptional gene-silencing and RNA interference: genetic immunity, mechanisms and applications

Abstract: This review summarises the development of our understanding of co-suppression in plants, and describes how co-suppression relates to similar post-transcriptional gene-silencing (PTGS) phenomena, and underlying genetic immunity mechanisms. These comparisons have enabled us to develop sophisticated models that go some way to explaining what causes co-suppression, and indicate that manipulation of the underlying mechanisms can provide the plant biotechnologist with new tools to control gene expression and silenci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 96 publications
(94 reference statements)
0
2
0
Order By: Relevance
“…The reason for the failure of N. europaea and M. capsulatus to synthesize functional α‐ketoglutarate dehydrogenase and the significance of this to their obligate physiologies remain to be established. Among the possibilities are: (i) failure to transcribe one or both of the genes into mRNA, (ii) deletion of regulatory parts of the operons, (iii) that the obligate nature of their central metabolism results from regulatory controls causing permanent repression of the genes, or (iv) some kind of post‐transcriptional gene silencing, possibly by endogenous small interfering RNAs [17,131].…”
Section: Testing the α‐Ketoglutarate Hypothesismentioning
confidence: 99%
“…The reason for the failure of N. europaea and M. capsulatus to synthesize functional α‐ketoglutarate dehydrogenase and the significance of this to their obligate physiologies remain to be established. Among the possibilities are: (i) failure to transcribe one or both of the genes into mRNA, (ii) deletion of regulatory parts of the operons, (iii) that the obligate nature of their central metabolism results from regulatory controls causing permanent repression of the genes, or (iv) some kind of post‐transcriptional gene silencing, possibly by endogenous small interfering RNAs [17,131].…”
Section: Testing the α‐Ketoglutarate Hypothesismentioning
confidence: 99%
“…Using plum (Prunus domestica L.) as a model, we have shown that through genetic transformation, stone fruits highly resistant to PPV can be developed (Scorza et al, 1994;Ravelonandro et al, 1997). This resistance is based on post-transcriptional gene silencing (PTGS) (Turner and Schuch, 2000) induced by the PPV coat protein transgene that was inserted into plum 120 (Scorza et al, 2001). In the current report we describe field tests developed in order to evaluate resistance to natural aphid vectored infection.…”
Section: Introductionmentioning
confidence: 99%